A record of fossil shallow‐water whale falls from Italy. (4th January 2014) - Danise, Silvia; Dominici, Stefano
<x xml:space="preserve">Abstract</x> Twenty‐five Neogene–Quaternary whales hosted in Italian museum collections and their associated fauna were analysed for evidence of whale‐fall community development in shallow‐water settings. The degree of bone articulation, completeness of the skeleton and lithology of the embedding sediments were used to gather information on relative water depth, water energy, sedimentation rate and overall environmental predictability around the bones. Shark teeth and hard‐shelled invertebrates with a necrophagous diet in close association with the bones were used as evidence of scavenging. Fossil bone bioerosion, microbially mediated cementation and other mollusc shells in the proximity of the remains informed on past biological activity around the bones. The results are consistent with the hypothesis that shallow‐water whale falls differ from their deep‐water counterparts. Taphonomic pathways are more variable on the shelf and whale carcasses may not go through all steps of the ecological succession as recognised in the deep sea. Whilst the mobile scavenger and the enrichment opportunistic stages are well represented, chemosynthetic taxa typical of the sulphophilic stage were recovered only in one instance. The presence of a generalist fauna among the suspension feeding bivalves and carnivorous gastropods, and the extreme rarity of chemosynthetic taxa, suggest that predatory pressure rules out whale‐fall specialists from shallow shelf settings as in analogous cold seep and vent shallow‐water communities.